Consumer loan rate dispersion and the role of competition: Evidence from Turkish banking industry - Selva Bahar Baziki; Yavuz Kılıç; Muhammed Hasan Yılmaz (Central Bank Review (CBR), 2022)
This paper investigates the degree of dispersion in the loan pricing of commercial banks and its association with competitive conditions in the banking industry of a large emerging economy. To quantify the lending rate variability in consumer loans, we utilize a new indexation mechanism exploiting a detailed bank-level dataset for the period January 2007-April 2020. With panel convergence methods, we show the existence of heterogeneity in long-term co-movements among banks' loan pricing, while periods following the tightening in financial conditions display short-term deviations from general tendencies as demonstrated by dispersion indices. Our empirical design also entails the construction of competition indicators for aggregated and consumer segment-based credit market developments. Quantile regression results validate that the improvements in industry competition are related to the lower level of lending rate dispersion in housing and vehicle segments in a statistically significant manner, whereas an opposite relationship is evident for general-purpose loans.
Keywords: C31; C33; G21; D40; 330; Loan rate dispersion; Competition; Log-t convergence test; Quantile regression